IpsDst of Dst Storms Applied to Ionosphere-Thermosphere Storms and Low- Latitude Aurora - Balan, N.; Zhang, Qing-He; Shiokawa, K.; Skoug, R.; Xing, Zanyang; Tulasiram, S.; Otsuka, Y. (My University, 2019)
Conventionally, the minimum value of Dst (DstMin) and maximum values of Kp and AE (Kpmax and AEmax) representing the geomagnetic storm intensities have been used for investigating space weather in Earth's environment. The present paper uses the derived parameters (IpsDst, IpsKp, and IpsAE) giving the mean values of Dst, Kp, and AE during the main phase (MP) of Dst storms for investigating ionosphereâ€ thermosphere storms and lowâ€ latitude (630 nm) aurora. The derived parameters (IpsDst, IpsKp, and IpsAE) representing the impulsive strength of geomagnetic storms seem to have more systematic dependence among themselves than among the intensities (DstMin, Kpmax, and AEmax). The ionosphereâ€ thermosphere storms observed by the CHAMP (Challenging Minisatellite Payload) satellite and lowâ€ latitude auroras observed by optical imagers are much more intense during high impulsive storms than high intensity storms. In a statistical sense, over 175 positive ionospheric storms (â–³NmF2) observed in 1985â€“2005 and the intensity of 20 red auroras observed in 1989â€“2004 at midlatitudes correlate better with the impulsive parameters than the intensity parameters, with the best correlation being with IpsDst. The mechanism of the impulsive action (highâ€ energy input over a short duration) leading to large IpsDst arises from the impact of fast solar storms (interplanetary coronal mass ejections) with large IMF Bz southward at their front (or shock). The impulsive action results in bright lowâ€ latitude auroras and strong ionosphereâ€ thermosphere storms.
Keywords: IpsDst storms; Dst storms; Ionosphere-thermosphere storms; Low latitude arurora